Developing Dynamics in the Mountain-Forest Zone of the Southern Urals from the Bronze Age to the Early Modern Time, based on Interdisciplinary Research at the Mouth of the Kan River - Evgenij V. Ruslanov; Nikita S. Savelev; Ravil G. Kurmanov (Археология евразийских степей)
Data is presented on all currently known settlement sites from the Bronze Age to the Modern Period, located in the mouth area of the Kana River (a mountain-forest zone in the southern part of the Ural Mountains, a major right tributary of the Belyia River). These sites were partially studied in 2018 by the South Ural Complex Archaeological Expedition of IIYaL UFIC RAN. Based on the obtained archaeological and paleoecological data, it has been established that the Belaya River valley, which essentially diagonally traverses the Southern Urals Mountains, did not function as a "Trans-Ural highway," as had been previously speculated. The dynamics of the development of the mountain valley of the Belaya River adhered the general principles traced at least from the Eneolithic to the Ethnographic time, which remained unchanged – the type of its development can be described as resource-based. Archaeologically, at the same time, the movement of a diverse population into the river valley is recorded from three main directions – from the Trans-Ural forest-steppe foothills (downstream, probably from the Beloretsk area), from the border of the steppe and the southern forest-steppe of the Urals, through the entrance to the mountain canyon (upstream) and from the steppes of the Trans-Urals (directly from the east, on the right small tributaries of the Belaya River).